2019
DOI: 10.15446/rfnam.v72n3.75730
|View full text |Cite
|
Sign up to set email alerts
|

Populations of Spodoptera frugiperda (Lepidoptera: Noctuidae) cause significant damage to genetically modified corn crops

Abstract: The fall armyworm (Spodoptera frugiperda (J.E. Smith)) is an important harmful pest for corn crops in Colombia. Knowing its population’s fluctuation regarding genetically modified plants allows the implementation of monitoring plans and time-effective management actions. The objective of this study was to establish the population’s fluctuation of S. frugiperda during 2014-2016 in the hybrids 30F35R and 30F35HR (genetically modified with the Cry1F endotoxin) in El Espinal, Tolima, Colombia. Accumulations in fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Our review of over 500 scientific publications related to fall armyworm damage revealed that four scales are most widely applied. They are the nominal "yes-no damage scale" (Gómez et al 2013;De La Rosa-Cancino et al 2016;Zibanda et al 2017;Midega et al 2018;Aguirre et al 2019;FAO and CABI 2019;Jaramillo-Barrios et al 2019;Maruthadurai and Ramesh 2020), the ordinal "Simple 1 to 5 whole plant damage scale" (Cruz and Turpin 1983;Figueiredo et al 2006;dal Pogetto et al 2012;Grijalba et al 2018;Fotso Kuate et al 2019;dos Santos et al 2020), "Davis' 0 to 9 whorl & furl damage scale" (Davis et al1992), and "Williams' whole plant 0 to 9 leaf damage scale for fall armyworm" (Williams et al 1989). As those scales all provide difficult-to-analyse nominal or ordinal (rank) data types, we created a novel 0.0 to 4.0 leaf damage index allowing finer, more linear, and therefore more accurate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of over 500 scientific publications related to fall armyworm damage revealed that four scales are most widely applied. They are the nominal "yes-no damage scale" (Gómez et al 2013;De La Rosa-Cancino et al 2016;Zibanda et al 2017;Midega et al 2018;Aguirre et al 2019;FAO and CABI 2019;Jaramillo-Barrios et al 2019;Maruthadurai and Ramesh 2020), the ordinal "Simple 1 to 5 whole plant damage scale" (Cruz and Turpin 1983;Figueiredo et al 2006;dal Pogetto et al 2012;Grijalba et al 2018;Fotso Kuate et al 2019;dos Santos et al 2020), "Davis' 0 to 9 whorl & furl damage scale" (Davis et al1992), and "Williams' whole plant 0 to 9 leaf damage scale for fall armyworm" (Williams et al 1989). As those scales all provide difficult-to-analyse nominal or ordinal (rank) data types, we created a novel 0.0 to 4.0 leaf damage index allowing finer, more linear, and therefore more accurate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Because of partial cross‐resistance between Cry1F and Cry1A.105 32,39 and the continued use of Bt maize technologies such as MON 89034 with limited compliance with structure refuge recommendations in Brazil, the ability of Bt maize pyramids based on these proteins to protect plants against FAW damage was reduced 32,49,61,62 . A similar outcome is expected in other regions in South America where FAW is the major maize lepidopteran pest and where resistance to commercially available Bt maize technologies has already been observed in FAW 37,63,64 . This chain of events considerably reduces the choices that growers have to effectively manage FAW.…”
Section: Discussionmentioning
confidence: 97%
“…The PD treatments and evaluation time were used as fixed effects and the block as a random effect. The best model was selected using the Akaike criterion with Bayesian information and maximum likelihood (Jaramillo- Barrios et al, 2019). The results only interpreted the factors and interaction that showed significant differences and the significant individual effects when the interaction did not show significant differences.…”
Section: Discussionmentioning
confidence: 99%